Income Growth, School Enrolment and the Gender Gap in Schooling: Evidence from Rural Pakistan (The Pakistan Development Review, 2014)
Household panel data document a remarkable closing of the gender gap in school enrolment in rural Pakistan between 2001 and 2004. During this 3-year period, there was an 8 point increase in the percentage of girls entering school, while the corresponding increase for boys was less than 2 percentage points. More than half of the rise for girls can be explained by the substantial increase in household incomes, whereas comparatively little is accounted for by increased school availability. Unpacking these enrolment trends and their determinants requires solving the classic period-age-cohort identification problem. The paper shows how to do so using auxiliary information on the distribution of school entry ages. JEL Classification: O15, O40, I 25, I21 Keywords: School Enrolment, Gender, Income Growth, Gender Gap